Electrical shock-induced atrial fibrillation - Stojanović, Milovan; Ilić, Bojan; Deljanin-Ilić, Marina; Ilić, Stevan (Vojnosanitetski pregled, 2023)
Introduction. An electrical injury can cause various cardiac arrhythmias, such as asystole, ventricular fibrillation, sinus tachycardia, and heart blocks. However, it rarely causes atrial fibrillation (AF). Case report. The 47-year-old patient was admitted to the Emergency Department after receiving an electric shock (
Keywords: anti-arrhythmia agents; atrial fibrillation; drug therapy; electric injuries; electrocardiography